Retrofitting in Fabric Finishing Machine - Sanforizadeira - Araújo, Madson do Nascimento; Guimarães Batista, Josias; Moreira, André Pimentel; Barbosa, Danielle Alves; da Silva, Linconl Lobo (Journal of Mechatronics Engineering, 2021)
With the advancement of technology in all fields, mainly in the industrial sector, which is manifested in more modern and self-contained equipment. Many equipment in the industry are obsolete with the electrical and electronic parts, but the mechanical parts are in perfect condition and can often be used for a long time. This paper demonstrates the retrofitting of a fabric finishing machine (Sanforizadeira) in the textile process thet was obsolete. In these conditions, it became necessary to retrofit the automation system. Through the study of the machine and the process, involving the fields of production and mechanical maintenance, the critical points and the improvements that should be implemented were found, thus raising the materials needed to carry out the work. The automation system was modernized, the control panels were replaced and improvements were implemented. The final result was achieved through the objectives outlined in this work, guaranteeing the company a system with considerable improvements, with a reduction in the number of stops and time spent for maintenance. The results were demonstrated by the graphs of the maintenance indicators. Comparing the before and after retrofitting, the following indicators were analyzed for six months: Failure rate, with an average reduction of 50% in the failure rate per hour; Mean time between failures, showed an average increase of 140 hours in the prediction of the next failures; Average time to repair, presented an average reduction of thirteen minutes in the resolution of the failures; Availability, there was a 16% increase in the availability of the machine, leaving the indicator above 90% where the ideal is 100%. Finally, the total cost of the project represented only 9.5% of the total value of a new machine, being also considered a positive result for the work.